1996
DOI: 10.1007/s002640050074
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic surgery and HIV disease in Africa

Abstract: Human immunodeficiency virus (HIV) infection has radically changed African orthopaedic practice within a decade. In Lusaka, a third of adults are infected, but most have no physical signs of the disease. Early experience showed that closed fractures healed normally, the risk of sepsis during osteosynthesis was increased and most open fractures became septic. Major orthopaedic surgery in HIV-positive patients has increased risks of sepsis which rise steeply in those with physical signs of HIV disease. Musculosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 4 publications
2
54
3
1
Order By: Relevance
“…This weakness arises because of loss to follow-up (21%) and limited length of follow-up (1 year). The only other study known to the authors that looks at late sepsis in fixation implants is by Jellis [9]. He noted late sepsis in ten such implants in HIVpositive patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This weakness arises because of loss to follow-up (21%) and limited length of follow-up (1 year). The only other study known to the authors that looks at late sepsis in fixation implants is by Jellis [9]. He noted late sepsis in ten such implants in HIVpositive patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that late sepsis occurs more commonly in patients whose immunity is compromised as a result of HIV disease [2,7,9,10,13]. Most such reports are based on follow-up of arthroplasties in haemophiliacs with HIV disease [7,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In coinfection of HIV and tuberculosis, where both conditions are of insidious onset and where reactive arthritis or septic arthritis are also common in HIV patients, the diagnosis of tuberculous arthritis and osteomyelitis becomes difficult (Chretien 1990;Elliott 1990;Govinder et al 2000;Jellis 1996;…”
Section: Introductionmentioning
confidence: 99%